2018
DOI: 10.3390/su10041253
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Competitiveness of Quanzhou Port on the Belt and Road in China Based on a Fuzzy-AHP and ELECTRE III Model

Abstract: Abstract:With the establishment of the Belt and Road national strategy, Quanzhou Port is a significant development opportunity. Quanzhou Port is the origin of the 21st century Maritime Silk Road and part of the Belt and Road, but as a pioneer project of the Maritime Silk Road and the main port in the Belt and Road strategy, its development has encountered some challenges and problems. Hence, this paper aims to evaluate the competitiveness of Quanzhou Port based on the criteria selected by experts and correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 38 publications
0
11
0
2
Order By: Relevance
“…However, they also believed in the future, they would interact again through reconstruction and renewal. (3) In the research on the port-city coordination, Llovera [25], Jeong [26], Jorrit [27], et al, selected ports in Latin America, Europe, Korea, Ghana and so on as their research objects. The effects of ports on urban spatial structure, policy and economy, and the impacts of urban morphology on port development were explored by the means of metrology and system dynamics so that better strategies and systems could be designed to facilitate the port-city coordination.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they also believed in the future, they would interact again through reconstruction and renewal. (3) In the research on the port-city coordination, Llovera [25], Jeong [26], Jorrit [27], et al, selected ports in Latin America, Europe, Korea, Ghana and so on as their research objects. The effects of ports on urban spatial structure, policy and economy, and the impacts of urban morphology on port development were explored by the means of metrology and system dynamics so that better strategies and systems could be designed to facilitate the port-city coordination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, ports and port cities are playing indispensable roles of crucial platforms in international trade. Additionally, China's implementation of the 21st Century Maritime Silk Road Initiative has helped to boost and upgrade ports and port cities [3] so that they are bearing greater responsibilities in international business. In turn, the port-city interaction will also foster international cooperation and promote the regional economic development so as to facilitate the initiative.…”
Section: Introductionmentioning
confidence: 99%
“…The example proved that IFAHP can be used to deal with more complex problems. Gao et al [28] used IFAHP to evaluated the port competitiveness of Quanzhou Port and pointed out directions for the future development. Dai et al [29] applied fuzzy group ideal point method to evaluate the sustainable development of power grid enterprises, and the results showed that the proposed method have the best performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most scholars affirm the positive impact of the "B&R" Initiative on the regional economy [9][10][11][12][13][14][15][16]. At the national level, some scholars believe that the "B&R" Initiative can promote the economic development of participating countries and indicate that investment in non-monopoly enterprises accounts for the majority of the investment in non-infrastructure investment [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%